Wilms tumor and neuroblastoma: indications and results of radiotherapy - Leborgne, R; Leborgne (h), F; Leborgne, J H; Baclocci, L A (Cirugía del Uruguay, 2020)
A series of 35 children with Wilm's 'tumours is presented. 28 of these cases have a follow-up of more than two years. 7 patients had no evidence of disease 2 to 10 years after treatment. preoperative irradiation of Wilm's tumours is advised, as a 60 % cure-rate in 5 patients was obtained with this technic. It is recognized that the group of patients with pr.eoperative irradiaion is very s?iall. A series of 14 children wih proved abdominal neuroblastoma is presented. Only 6 cases were able to be treated by radiotherapy, and only one is living with no evidence of disease 2 years and a half later.